Comparison of low-dose ketamine to methadone for postoperative pain in opioid addicts: a randomized clinical trial - Elham Bakhtiari; Mehrdad Mokaram Dori; Millad Reza Darban Razavi; Andia Peivandi Yazdi; Arash Peivandi Yazdi (Anesthesia and Pain Medicine)
Background Postoperative pain can lead to several complications. The effectiveness of different opioids in relieving pain after surgery has been widely studied. However, managing pain in patients with opioid addiction is still challenging. This study aimed to examine the impact of ketamine and methadone on postoperative pain in patients with addiction. Methods This was a non-inferiority randomized clinical trial. All included patients were monitored for morphine use, pain scores, and vital signs every 3 h. The intervention group received 0.5 mg/kg ketamine administered intravenously every 6 h. The control group received 5 mg of methadone intramuscularly every 8 h. The patient received intravenous morphine if their visual analog scale was above 3. All side effects in each group were recorded. Results Two hundred and twenty patients were included in this study. There were 127 men (57.7%) with an average age of 57.1 ± 19.5 and 93 women (42.3%) with an average age of 57.1 ± 21.0. There were no significant differences in demographic characteristics between the groups. There was no significant difference in the dose or frequency of morphine administration between groups. There was no significant difference between the groups in pain scores and vital signs at different time points. Drug side effects, including delirium and gastrointestinal symptoms, did not differ significantly between the methadone and ketamine groups. Conclusions Our clinical data support the hypothesis that ketamine is not inferior to methadone in patients with addiction. Future Randomize Clinical Trials are needed to confirm these observations.